Success and failure of countries at the Olympic Games, - Reiche, D. (Routledge, 2016)
One of the first opinions I received from a friend in response to the idea of my book was that the Olympic Games are generally negative because of the notion that "Olympic athletes all ruin their health." Although this opinion might stem from a general bias against sport, I had to admit it might still be a valid question worth studying. However, such normative discussion is not the center of focus for this book. Rather than discussing whether elite sport is good or bad, I seek to analyze why winning medals at the Olympic Games has become a priority around the world. As a political science professor, I find it interesting to analyze this phenomenon because Olympic success has become an area of increased government involvement in many countries, with considerable resources from state budgets being channeled into policies that promote national success at the greatest international sporting event. This book seeks to answer the following questions: how "Olympic success" is defined differently around the globe, why countries are aiming for success at the Games and its Winter and Summer editions, and which policy instruments are countries utilizing to achieve their sporting goals. During the last decade I have worked as a professor in Lebanon and the United States, however my childhood in Germany played an important role for my interest in the topic of this book. After telling my father about plans to write a book on success and failure of countries at the Olympics, he was adamant that I discuss the role of the German Democratic Republic (GDR). The GDR, better known internationally as East Germany, was a sporting power despite its short period of existence. "We" in West Germany, the Federal Republic of Germany (FRG), had to acknowledge that our East German "brothers and sisters" outperformed us at the Olympic Games. Although there were severe travel restrictions from the West to the East (and even more restrictions vice versa), it remained possible to access East German TV in the northern German city of Hanover where I grew up. I can still remember East German commentators enthusiastically celebrating the successes of their athletes.